Pengaruh Keamanan Dan Kemudahan Terhadap Keputusan Pembelian Tiket Pesawat Pada Aplikasi Traveloka Di Kota Batam - Kristina Puja; Muhammad Haldy (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to analyze the influence of security and ease of use on airline ticket purchase decisions through the Traveloka application in Batam City. The rapid development of digital technology has increased people's reliance on online travel service applications, making transaction security and ease of use important factors influencing purchase decisions. This study employed a quantitative research approach by distributing questionnaires to Traveloka users in Batam City who had previously purchased airline tickets through the application. The collected data were analyzed using multiple linear regression to examine the effect of each independent variable on purchase decisions. The findings reveal that security has a positive and significant effect on purchase decisions, as reflected in users' trust in the protection of personal data and the security of the payment system. Ease of use also has a positive and significant effect, demonstrated by the application's user-friendly navigation, fast access, and convenient booking process. Simultaneously, both security and ease of use make a significant contribution to airline ticket purchase decisions through the Traveloka application in Batam City. These findings highlight the importance of continuously enhancing security features and improving ease of use to maintain customer satisfaction and strengthen user loyalty.